2020
DOI: 10.1136/vr.105788
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial translocation in horses with colic and the potential association with surgical site infection: a pilot study

Abstract: BackgroundSurgical site infection (SSI) is a leading cause of morbidity in horses undergoing emergency exploratory laparotomy for the treatment of acute colic. The exact mechanism by which SSI develops in these cases is unclear. This prospective observational study investigated whether bacterial translocation occurs in horses with acute colic and if there is an association between bacterial translocation and development of SSI.MethodsPeripheral venous blood (PVB) and peritoneal fluid (PF) samples were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…In three different studies, conducted in two different equine hospitals, shedding rates were shown to increase by 2.5-5.1-fold during hospitalization, implying that the nosocomial acquisition and spread of these resistant bacteria is common in certain veterinary facilities [11,16,17]. Moreover, there are numerous reports on various severe and invasive 3GCRE infectious syndromes among horses, e.g., skin and soft tissue infections, surgical site infections, upper respiratory tract infections, and bacteremia [18][19][20][21]. Furthermore, in horses, synovial infection with multidrug-resistant (MDR) bacteria was significantly associated with euthanasia [22].…”
Section: Introductionmentioning
confidence: 99%
“…In three different studies, conducted in two different equine hospitals, shedding rates were shown to increase by 2.5-5.1-fold during hospitalization, implying that the nosocomial acquisition and spread of these resistant bacteria is common in certain veterinary facilities [11,16,17]. Moreover, there are numerous reports on various severe and invasive 3GCRE infectious syndromes among horses, e.g., skin and soft tissue infections, surgical site infections, upper respiratory tract infections, and bacteremia [18][19][20][21]. Furthermore, in horses, synovial infection with multidrug-resistant (MDR) bacteria was significantly associated with euthanasia [22].…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Bacteraemia has also been identified with blood culture in horses with colitis, some colic cases, and post-endodontic procedures. [29][30][31][32] Published procedures for blood culture collection in adult horses also vary. Commonly described protocols are similar to those described in foals (Table 1), though larger volumes of blood are collected in some cases, and collection from multiple sites (e.g.…”
Section: Horsesmentioning
confidence: 99%
“…both jugular and/or cephalic veins) is more commonly performed in horses than in foals. [29][30][31]…”
Section: Horsesmentioning
confidence: 99%
See 2 more Smart Citations